(untitled) (KULT_online, 2016)
Using a hybrid theoretical approach, Robert Gutouing examines the processes of knowledge production in digital networks. The explanatory models used are illustrated by exploratory analysis of two knowledge networks: open source software production as well as the online encyclopedia, Wikipedia. The socio-political and ethical dimensions that arise are taken into consideration. The overall goal of this article is to re-evaluate the issues raised by the question Jean-François Lyotard posed in 1979, about knowledge in post-industrial societies, which in recent decades evolved into a knowledge-based networking society.